Evolutionary game and simulation analysis of tripartite subjects in public health emergencies under government reward and punishment mechanisms - Dandan Gao; Wei Guo (Scientific Reports)
Abstract Public health emergencies are critical to people’s lives and health, economic development and social stability. Understanding how to respond correctly to public health emergencies is the focus of societal attention. This paper focuses on the tripartite entities of public health emergencies: local governments, pharmaceutical enterprises and the public. On the basis of the assumption of finite rationality, it delves into the game-theoretic interaction among these groups during such crises. By constructing an evolutionary game model, this paper analyses the dynamic adjustment process of the decision-making behaviors of these three parties, leading to the identification of evolutionarily stable strategies for the local government, pharmaceutical enterprises, and the public under different conditions. Moreover, MATLAB is used to carry out simulation experiments to analyse the influence of the local government’s reward and punishment mechanism on the strategic choices of the involved parties in the game. The research findings indicate that (1) For the tripartite entities of public health emergencies, the key for strategy choices is to reduce the gain obtained from illegal production and non-cooperation with prevention and control. (2) The strength of the initial willingness to participate has a significant effect on the evolution strategies of each subject. (3) For pharmaceutical companies and the public, the incentives and penalties of local governments can promote the former’s compliance and the latter’s cooperation in prevention and control. Based on these results, countermeasure suggestions to promote mutual collaboration among local governments, pharmaceutical enterprises, and the public to jointly respond to public health emergencies are proposed.